2023
DOI: 10.1111/aor.14590
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes with cangrelor plus aspirin versus oral dual antiplatelet therapy in patients supported with venoarterial extracorporeal membrane oxygenation

Abstract: BackgroundPatients with refractory cardiogenic shock from an acute myocardial infarction may receive percutaneous coronary intervention (PCI) and require the use of venoarterial extracorporeal membrane oxygenation (VA–ECMO). The purpose of this study was to compare bleeding and thrombotic events in patients treated with cangrelor plus aspirin versus oral dual antiplatelet therapy (DAPT) while supported with VA–ECMO.MethodsWe conducted a retrospective review of patients who received PCI, were supported with VA–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Similar to our study, previous studies in patients with MCS on cangrelor have demonstrated higher bleeding events than thrombotic events with major bleeding occurring in 21–77% of patients and thrombotic events in 10–35% of patients. 4 6 , 12 Therefore, additional focus is needed to better reduce bleeding events while preventing thrombotic events. Utilizing PFT-guided cangrelor dosing in our study allowed for lower cangrelor dosing while maintaining adequate antiplatelet activity, which may reduce bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our study, previous studies in patients with MCS on cangrelor have demonstrated higher bleeding events than thrombotic events with major bleeding occurring in 21–77% of patients and thrombotic events in 10–35% of patients. 4 6 , 12 Therefore, additional focus is needed to better reduce bleeding events while preventing thrombotic events. Utilizing PFT-guided cangrelor dosing in our study allowed for lower cangrelor dosing while maintaining adequate antiplatelet activity, which may reduce bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies in patients supported with VA-ECMO or as bridging therapy used empiric cangrelor dosing of 0.75 mcg/kg/min based on similar dosing used in the BRIDGE trial. 4 , 5 , 7 11 Other studies allowed for lower cangrelor doses between 0.5 and 0.75 mcg/kg/min 12 , 13 with PRU monitoring or empiric dosing as low as 0.125 mcg/kg/min in one study of patients supported on VA-ECMO. 6 In our study, we utilized an initial dose of 0.75 mcg/kg/min with subsequent dose adjustments based upon PRU values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation